Phase-field simulation study of dendritic growth in directional solidification of Fe-C alloy under varied initial solute concentrations - Hong-bo Zeng; Xin-gang Ai; Ming Chen; Rui Guan; Qing-song Chen; Zhong-lin Hou (Materials Research Express)
As a method to control the solidification process of metal to optimize the microstructure, directional solidification technology is a common and effective way to improve the axial mechanical properties of alloy. In this paper, the dendrite growth process during isothermal directional solidification is simulated by using Kim-Kim-Suzuki (KKS) phase field model (PF model). The effect of different initial solute concentrations on the microscopic morphology of isothermal directionally solidified dendrites under uniform distribution conditions is investigated. In addition, considering the non-uniform distribution of solutes in real environments, the evolution of directionally solidified dendrites under conditions of vertical, parallel, and localized solute distribution is explored. The results indicate that the lower the initial solute concentration, the denser the dendrites. There is a quantitative relationship between the stable growth rate of directionally solidified dendrites and the initial solute concentration: v = −113372.4 c + 880. When dendrites move from a region of low initial solute concentration to a region of high concentration, they transition from dense to sparse. The difference in solute concentration vertical to the solidification direction causes the primary dendrite arms in the adjacent regions of parallel boundary line to tilt in their growth, and the degree of tilt increases with increasing differences in solute concentration. When the local solute concentration reaches 0.0075 mole, the growth of columnar dendrites is significantly hindered, leading to the occurrence of annihilation. As the solute concentration and the size of the local regions increase, the number of annihilated directionally solidified dendrites increases, and the development of secondary dendrites on the sidewalls of adjacent dendrites is enhanced. This phenomenon becomes more pronounced the closer the solute non-uniform regions are to the root positions of the dendrites.